2007
DOI: 10.1152/ajpheart.00123.2007
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypothermia (30°C) maintains myocardial integrity and modifies response of cell survival proteins after reperfusion

Abstract: Hypothermia preserves myocardial function, promotes signaling for cell survival, and inhibits apoptotic pathways during 45-min reperfusion. We tested the hypothesis that signaling at the transcriptional level is followed by corresponding proteomic response and maintenance of structural integrity after 3-h reperfusion. Isolated hearts were Langendorff perfused and exposed to mild (I group; n = 6, 34 degrees C) or moderate (H group; n = 6, 30 degrees C) hypothermia during 120-min total ischemia with cardioplegic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…There was less injury with arrest effect than in the 34-35°C, and the recovery was lower than in the 29-30.5°C arrest ( p < 0.05). The current results are in accordance with previous observations in the isolated rabbit hearts (Ning et al, 1998a(Ning et al, , 2007b.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…There was less injury with arrest effect than in the 34-35°C, and the recovery was lower than in the 29-30.5°C arrest ( p < 0.05). The current results are in accordance with previous observations in the isolated rabbit hearts (Ning et al, 1998a(Ning et al, , 2007b.…”
Section: Resultssupporting
confidence: 94%
“…The point around 30.5-31°C is similar to the protective temperature threshold in the isolated rabbit hearts (Ning et al, 1998b(Ning et al, , 1998c(Ning et al, , 2002. Accompanied with marked functional improvement, histological evidence showed that the hypothermia-treated hearts had less swelling and damage to the myocardium, as well as less collagen in the connective tissue (Ning et al, 2007b).…”
Section: Fig 5 Hr After Optimal Hypothermic Arrest (Mean -Se)mentioning
confidence: 58%
See 3 more Smart Citations